The role of communication and collaboration in business management - Mammadova, F.; Abdullayeva, N.; Мамедова, Ф. А.; Абдуллаєва, Н. К. (Харківський національний автомобільно-дорожній університет, 2025)
Communication and collaboration are fundamental components of effective business management, driving organizational alignment, innovation, and productivity. Clear communication ensures that information flows smoothly across all levels of an organization, enabling employees to understand goals, expectations, and strategies. Collaboration, on the other hand, brings together diverse perspectives and skills, fostering creativity and enabling teams to solve complex challenges more effectively. In a rapidly changing business environment, digital communication and collaboration tools have become essential, allowing teams to coordinate in real-time and adapt quickly to evolving market conditions. Together, these practices enhance decision-making, streamline processes, and create a culture of trust and teamwork, ultimately contributing to sustainable growth and a competitive edge. As organizations continue to evolve, prioritizing communication and collaboration will be critical for maintaining agility, innovation, and long-term success. This article explores the role of communication and collaboration in business management, with a particular focus on the use of digital technologies to optimize these processes. The paper analyzes how effective communication and teamwork are fundamental factors of organizational success, influencing productivity, decision-making, and organizational culture. Modern digital tools, such as messaging platforms, video conferencing, and collaborative platforms, are examined for their significant impact on accelerating team interaction, improving process transparency, and facilitating faster decision-making. The paper also discusses aspects such as the use of cloud services for centralized information storage, integration of various work tools, and ensuring flexibility through digital technologies. The impact of these technologies on business practices is considered, with an emphasis on remote work, project management, and employee feedback. The article identifies both the benefits and challenges associated with the implementation of digital communication technologies, including the risks of information overload and the difficulty of maintaining interpersonal relationships in virtual environments. Recommendations for the optimal use of digital solutions to enhance communication and collaboration in organizations are provided, ultimately contributing to sustainable growth and the competitiveness of the company.
Роль комунікації та співпраці в управлінні бізнесом
Keywords: Data analysis; strategic planning; financial forecasting; marketing; business management; аналіз даних; стратегічне планування; фінансове прогнозування; маркетинг; управління бізнесом; 316.773:070.1; 10.30977/ЕТК.2225-2304.2025.45.196